Diazepam Accelerates GABAAR Synaptic Exchange and Alters Intracellular Trafficking - Lorenz-Guertin, Joshua M.; Bambino, Matthew J.; Das, Sabyasachi; Weintraub, Susan T.; Jacob, Tija C. (Frontiers in Cellular Neuroscience, 2019)
Despite 50+ years of clinical use as anxiolytics, anti-convulsants, and sedative/hypnotic agents, the mechanisms underlying benzodiazepine (BZD) tolerance are poorly understood. BZDs potentiate the actions of gamma-aminobutyric acid (GABA), the primary inhibitory neurotransmitter in the adult brain, through positive allosteric modulation of γ2 subunit containing GABA type A receptors (GABAARs). Here we define key molecular events impacting γ2 GABAAR and the inhibitory synapse gephyrin scaffold following initial sustained BZD exposure in vitro and in vivo. Using immunofluorescence and biochemical experiments, we found that cultured cortical neurons treated with the classical BZD, diazepam (DZP), presented no substantial change in surface or synaptic levels of γ2-GABAARs. In contrast, both γ2 and the postsynaptic scaffolding protein gephyrin showed diminished total protein levels following a single DZP treatment in vitro and in mouse cortical tissue. We further identified DZP treatment enhanced phosphorylation of gephyrin Ser270 and increased generation of gephyrin cleavage products. Selective immunoprecipitation of γ2 from cultured neurons revealed enhanced ubiquitination of this subunit following DZP exposure. To assess novel trafficking responses induced by DZP, we employed a γ2 subunit containing an N terminal fluorogen-activating peptide (FAP) and pH-sensitive green fluorescent protein (γ2pHFAP). Live-imaging experiments using γ2pHFAP GABAAR expressing neurons identified enhanced lysosomal targeting of surface GABAARs and increased overall accumulation in vesicular compartments in response to DZP. Using fluorescence resonance energy transfer (FRET) measurements between α2 and γ2 subunits within a GABAAR in neurons, we identified reductions in synaptic clusters of this subpopulation of surface BZD sensitive receptor. Additional time-series experiments revealed the gephyrin regulating kinase ERK was inactivated by DZP at multiple time points. Moreover, we found DZP simultaneously enhanced synaptic exchange of both γ2-GABAARs and gephyrin using fluorescence recovery after photobleaching (FRAP) techniques. Finally we provide the first proteomic analysis of the BZD sensitive GABAAR interactome in DZP vs. vehicle treated mice. Collectively, our results indicate DZP exposure elicits down-regulation of gephyrin scaffolding and BZD sensitive GABAAR synaptic availability via multiple dynamic trafficking processes.